Assessment of Cardiovascular Autonomic Functions to Predict Development of Pregnancy Induced Hypertension - Kapoor, Nandini; Sharma, Rajeev; Ashat, Munish; Huria, Anju; Mishra, Ghansham (Nepal Journal of Obstetrics and Gynaecology, 2011)
Aim: This study aimed at performing autonomic function tests to predict PIH at early stage of pregnancy. Methods: 200 pregnant women between 12 to 20 weeks of gestation were selected for study. Handgrip dynamometer test (HGT) and Cold pressor test (CPT) were performed to assess sympathetic cardiovascular functions. Result: It was observed that 31 women out of 200 pregnant women developed PIH subsequently. ROC curve analysis was done to find out cut off values of high sensitivity and specificity for rise in systolic blood pressure (_SBP) and diastolic blood pressure (_DBP) during CPT and HGT. It was observed that out of 31 women who developed PIH/PE, 87.1% had _SBP _14mm Hg (cut off value) and 83.9% had _DBP _10mm Hg (cut off value) during CPT, both of which were statistically significant (p<0.001). Similarly for HGT, 31 women who developed PIH, _SBP _16 mm Hg and _DBP _14 mm Hg (cut off values) was observed in 96.8% and 83.9% women respectively (p< 0.001). Discriminant analysis showed that the reliability of both the tests in predicting PIH was very high (p<0.001). Conclusion: Thus it can be concluded from the study that heightened blood pressure response to physiological stimuli like cold and isometric exercise early in pregnancy could be used as a suitable tool to predict development of PIH. Key words: Cold pressor test, early detection, Handgrip dynamometer test, PIH DOI: http://dx.doi.org/10.3126/njog.v6i1.5251 NJOG 2011; 6(1): 41-45